C−H Oxygenation Reactions Enabled by Dual Catalysis with Electrogenerated Hypervalent Iodine Species and Ruthenium Complexes. Issue 8 (9th January 2020) - Massignan, Leonardo; Tan, Xuefeng; Meyer, Tjark H.; Kuniyil, Rositha; Messinis, Antonis M.; Ackermann, Lutz
Abstract: The catalytic generation of hypervalent iodine(III) reagents by anodic electrooxidation was orchestrated towards an unprecedented electrocatalytic C−H oxygenation of weakly coordinating aromatic amides and ketones. Thus, catalytic quantities of iodoarenes in concert with catalytic amounts of ruthenium(II) complexes set the stage for versatile C−H activations with ample scope and high functional group tolerance. Detailed mechanistic studies by experiment and computation substantiate the role of the iodoarene as the electrochemically relevant species towards C−H oxygenations with electricity as a sustainable oxidant and molecular hydrogen as the sole by‐product. para ‐Selective C−H oxygenations likewise proved viable in the absence of directing groups. Abstract : Dual catalysis : The joint action of catalytic amounts of iodoarenes, ruthenium(II) carboxylates, and electricity enables the expedient C−H oxygenation of amides and ketones by weak coordination.